2012
DOI: 10.1007/s10147-012-0447-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies and safety of neoadjuvant gemcitabine plus carboplatin followed by immediate cystectomy in patients with muscle-invasive bladder cancer, including those unfit for cisplatin: a prospective single-arm study

Abstract: Neoadjuvant GCarbo therapy followed by immediate RC is safe, even in cisplatin-unfit patients, and provides a favorable pathological cancer-free state. The single-arm single-institution study design and relatively short observation period were limitations of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 24 publications
1
50
0
1
Order By: Relevance
“…The use of carboplatin in a neoadjuvant setting and the optimal number of courses still are being debated [15][16][17][18][19][20]. Because no evidence clearly supports the superiority of a cisplatin-based against a carboplatinbased regimen in a neoadjuvant setting in patients with UTUC [16,21], we designed a strategy including carboplatin-based NAC followed by immediate surgery in patients with UTUC and impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The use of carboplatin in a neoadjuvant setting and the optimal number of courses still are being debated [15][16][17][18][19][20]. Because no evidence clearly supports the superiority of a cisplatin-based against a carboplatinbased regimen in a neoadjuvant setting in patients with UTUC [16,21], we designed a strategy including carboplatin-based NAC followed by immediate surgery in patients with UTUC and impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The use of neoadjuvant chemotherapy (NAC) for patients with renal impairment remains unclear [29][30][31][32][33]. Based on several guidelines [34,35] NAC was not recommended in the patients with CKD (= cisplatin-unfit) and carboplatin-based regimen was believed less effective than cisplatin.…”
Section: Risk-score-based Protocol Months After Rcmentioning
confidence: 99%
“…7 The GCarbo regimen has also been studied as perioperative chemotherapy, specifically neoadjuvant chemotherapy, in locally advanced bladder cancer prior to cystectomy. 8,9 Current bladder cancer guidelines, however, recommend against the substitution of carboplatin for cisplatin in the setting of perioperative chemotherapy and suggest consideration of split-dose administration of cisplatin for patients with renal dysfunction, although efficacy of this adjustment remains unproven. 7 …”
Section: Indication(s)mentioning
confidence: 99%
“…In the trials reviewed, neutropenia was reported in 50% to 100% [1][2][3]6,8,9 of patients and grade 3 to 4 neutropenia in 7% to 70% [1][2][3][4][5][6]8,9 of patients. Febrile neutropenia was reported in 3% to 25% of patients.…”
Section: Supportive Care a Acute And Delayed Emesis Prophylaxismentioning
confidence: 99%